The Effect of Paclobutrazol Concentrations in Different Shade Levels on Coleus Plant Leaves Color - Maretha Widhya Aulyaa Gusmawan; Sitawati Sitawati; Anna Satyana Karyawati (The University of Lampung, 2022)
Coleus scutellarioides is a leaf ornamental plant that is widely used as an ornamental plant in tourist attractions because it has an interesting leaf color. The purpose of study was to obtain right concentration of paclobutrazol for the brightness of the color of the leaves of the coleus plant in shaded conditions. The method used is a Split Plot Design with two factors, light intensity as the whole plot and paclobutrazol concentration as a split plot. The whole Plot consists of 3 levels, namely I100 (100% sunlight intensity), I75 (75% sunlight intensity) and I50 (50% sunlight intensity) while the split plot consisted of P0 (Without Paclobutrazol), P40 (Paclobutrazol 40 ppm), P80 (paclobutrazol 80 ppm) and P120 (paclobutrazol 120 ppm. The results showed there were interactions from the treatment of paclobutrazol concentrations at various light intensities. The application of paclobutrazol 0 ppm at a light intensity of 75% and 50% gave the same chlorophyll content results as the 100% light intensity treatment and 0 ppm paclobutrazol concentration.The conclusions in addition of paclobutrazol 40-80 ppm at a decrease in light intensity of 75% and 50% gives the result of anthocyanin content and leaf color equal to 100% intensity and paclobutrazol 0 ppm.keyword: Coleus, Shades, Color, Paclobutrazol, Konsentrastion